EARLY PERMIAN FUSULINIDS FROM THE CENTRAL PAMIR - Leven, Ernst (My University, 1993)
An endemic fusulinid assemblage is herein first described from Sakmarian rocks of the Central Pamir. It consists of 42 species and subspecies belonging to the genera Pseudofusulina, Sphaeroschwagerina, Paraschieagerina, Zellia, Robustoschwagerina, Eoparafusulina, Schubertella, Pseudoendothyra and Pseudoreichelina; 24 species and subspecies are newly named. Comparative studies of the above assemblage and the fusulinid fauna from other regions show that the former is characteristic of the peri-Gondwana area of the Tethys. The endemic elements recognized in the assemblage apparently are related to climatic factors.
Keywords: Permian; Fusulinida; Palaeogeography; Taxonomy; Pamir; Karakorum; Hindu Kush; Paleozoic::Permian; Палеозой::Пермская